High‐throughput tandem‐microwell assay for ammonia repositions FDA‐Approved drugs to inhibit Helicobacter pylori urease. Issue 11 (6th October 2021) - Liu, Fan; Yu, Jing; Zhang, Yan‐Xia; Li, Fangzheng; Liu, Qi; Zhou, Yueyang; Huang, Shengshuo; Fang, Houqin; Xiao, Zhuping; Liao, Lujian; Xu, Jinyi; Wu, Xin‐Yan; et al.
Abstract: To date, little attempt has been made to develop new treatments for Helicobacter pylori ( H . pylori ), although the community is aware of the shortage of treatments for H . pylori . In this study, we developed a 192‐tandem‐microwell‐based high‐throughput assay for ammonia that is a known virulence factor of H . pylori and a product of urease. We could identify few drugs, that is, panobinostat, dacinostat, ebselen, captan, and disulfiram, to potently inhibit the activity of ureases from bacterial or plant species. These inhibitors suppress the activity of urease via substrate‐competitive or covalent‐allosteric mechanism, but all except captan prevent the antibiotic‐resistant H . pylori strain from killing human gastric cells, with a more pronounced effect than acetohydroxamic acid, a well‐known urease inhibitor and clinically used drug for the treatment of bacterial infection. This study offers several bases for the development of new treatments for urease‐containing pathogens and to study the mechanism responsible for the regulation of urease activity.